THE EFFECT OF READING FROM THE PRINTED MATERIAL AND THE PROJECTION SCREEN ON REMEMBRANCE COMPREHENSION AND ATTENTION SKILLS OF THE TEACHER CANDIDATES - Murat TUNCER (Fırat University, 2019)
In this study, it has been struggled to relatively explain clearly this problem by being searched the situation in terms of reading on the printed material and projection screen. The teacher nominees are presented the text selected to show this aim on both the printed material and the projection screen. The questions are addressed to the stated text have been converted into success point. The points gained have been compared. From this aspect, the research has been carried out according to the static group comparison design which is one of the experimental designs. The sample consists of 214 students who study in education faculty in the department of primary school, Turkish, art, social sciences, religious culture and moral knowledge teaching. With a randomly selection, 92 student was appointed as experiment group,122 students was appointed as control group so experiment group which consists of 92 students was determined as the group who reads from the projection screen and the group which consists of 112 students was determined as the group who reads from the printed materials. In the point of recollection ability, one of the findings of the research is that there is a significant difference on behalf of the students who reads printed materials between the success grades of the groups who read from the printed materials and projection screen. In the point of comprehension ability, a significant difference has been found between the Primary school and Turkish teaching groups according to the success grades of projection screen. Students in the skill of attention from the printed materials can be said to be more successful. It is considered that teacher training is very important in the use of technology in the classroom. Therefore, it is estimated that it will be useful to be given courses about how the technology will affect on the training activities in the teacher training.